A case study on the impact of leadership styles on influencing employees' job satisfaction in Infopro Sdn.Bhd. Petaling Jaya / Fateen Atiqah Saifudin - Saifudin, Fateen Atiqah (Faculty of Business and Management, 2013)
Leadership is a process of influencing between leaders and subordinates where a leader attempts to influence the behavior of subordinates to achieve the organizational goal. Organizational success in achieving its goals and objectives depends on the leaders ofthe organization and their leadership style. By adopting the appropriate leadership styles, leaders can affect employee job satisfaction, commitment, morality and productivity. There are two hundred INFOPRO Sdn. Bhd. employees working in the Petaling Jaya branch and one hundred and thirty-two of the employees voluntarily participated in this study. Three types of leadership styles, namely, transformational, transactional and laissez-faire were found to have direct relationship with employees' job satisfaction.. The objectives of the research were firstly, to identify the current status of employees' job satisfaction in INFOPRO Sdn. Bhd. and the second objective was to examine the relationship between transformational, transactional and laissez-faire leadership style on INFOPRO Sdn. Bhd. employees' job satisfaction. Regarding to these objective, two research questions has been developed. This study was carried out by using correlation design method where is to find the relationship between the independent variable and dependent variable where in this case the independent is the leadership styles and the dependent variable is the employees job satisfaction. The method used to collect data was by distributing questionnaire to one hundred and thirty-two employees. The sampling procedure that was being used was simple random sampling where these one hundred and thirty-two sets of questionnaires were distribute randomly to employees in varies departments. One hundred and thirty-two questionnaires were distribute but only one hundred questionnaires were returned. The results showed that transformational leadership style has a stronger relationship with job satisfaction rather than transactional and laissez-faire leadership styles. This implies that transformational leadership is perfectly suitable for the organization. Implications of the findings were discussed further. In conclusion, it was found that the main factor that contributes to INFORPRO Sdn. Bhd. employees job satisfaction is social bound between the employees and their colleagues moreover their leaders or in other words how they are being treated by others at work. However, from the analysis, it can be stated that INFOPRO employees has accepted transformational leadership style and this might bring huge impact if the leadership style change to transactional leadership style or laissez-faire where employees might not be able to accept the changes of structure that they are comfortable with.